2022
DOI: 10.37649/aengs.2022.176366
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Corroded Longitudinal Steel Bars on Flexural Behavior of Reinforced Concrete Beams

Abstract: This study aims to examine the relationship between the corrosion rate of longitudinal tensile steel bars and the maximum flexural strength of reinforced concrete RC beams. The study's methodology is designed to show the structural behavior of corroded and non-corroded RC beams, such as ultimate load, deflection, stiffness, crack patterns, and failure mode. Three rectangular beams were cast with dimensions (150× 200 ×1200) mm, and all specimens have the same amount of longitudinal and transverse reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…At the same time, the value of deflection at the midspan for ultimate loads was reduced by 8,4 % compared to the control beam. Mahmood and Lateef (9) , Fayaad et al (39) and Triantafyllou et al (40) were the researchers whose access to these findings was closed. The experimental results demonstrated that the corroded RC beam had a less ductile failure mode than a control beam at the same age.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the value of deflection at the midspan for ultimate loads was reduced by 8,4 % compared to the control beam. Mahmood and Lateef (9) , Fayaad et al (39) and Triantafyllou et al (40) were the researchers whose access to these findings was closed. The experimental results demonstrated that the corroded RC beam had a less ductile failure mode than a control beam at the same age.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, data showed that the deeper the fractures, the more important they are, which may lead to crack propagation, with all three forms of interaction shown to be identical to what was discovered [11] for internal and exterior cracks in a plate. In terms of the influence of vibrational loading on a cracked component [12][13][14][15] have considered this problem. Previously, Zhang [16,17] used Crack-Tip Opening Displacement (CTOD) to perform 3-D FEA on a circumferentially cracked pipe containing a semi-elliptical surface crack and an elliptical embedding crack.…”
Section: Introductionmentioning
confidence: 99%